Topological solitons in branched aliphatic molecules. (13th April 2018) - Tkachev, Sergii Yu.; Alekseev, Olexander M.; Lazarenko, Maxim M.; Lazarenko, Myhailo V.; Kovalov, Kostiantyn M.; Bokhvan, Serhii I.; Grabovskii, Yurii E.; Hoshylyk, Nataliia V.
ABSTRACT: Polymorphic transitions are typical for molecular crystals of long chain aliphatic compounds. In the present work we studied the possibility of polymorphic transitions via the mechanism of topological solitons. The solitons correspond to stretching/compression of aliphatic chain by a half of the period, accompanied by 180° turn in branched molecules. Triacyglycerides (TAG) were chosen as an object of study; temperature dependencies of the specific heat capacity at constant pressure, complex dielectric permittivity, spectral (IR) and structural (powder XRD) properties of TAGs were characterized performed at −170 ÷ 70°C. Following model was proposed to explain the experimental results. Thermal transformations of TAGs started from initiation of topological solitons on the methyl groups. The solitons passed along the alkyl chains and reoriented the ester groups, resulted in thermal dipole-relaxation polarization defrost observed as a relaxation process in the range (−80÷0)°C. Reaching the stoichiometric obstruction (branching), the solitons reflect from it. When the temperature increases up to 60°C, melting of TAG polycrystals takes place.